Complete guide to growing and cultivating herbs & spices : expert advice for planting indoors and outdoors, the best containers, and storage - Gray, Linda, 1948- (IMM Lifestyle Books, 2024)
"Inside this home gardening book, author Linda Gray steers you through every step of planning indoor and outdoor gardens, from propagating and growing to using and preserving herbs and spices. This isn't a one-size-fits-all guide! It's a comprehensive resource to discover what fits your unique space and climate. You'll discover plant-specific advice to target the best possible additions to your garden, including strategies for selecting which herbs and spices to grow, prepping your space at home, and designing to maximize your space. Each plant profile explains the specific challenges and advantages of each plant and how to select the best for your climate, along with growing, planting, and harvesting advice, as well as how to use each herb and spice in food." --